A review of the Ghana Planting for Food and Jobs program: 2017-2020: Implementation, impact, and further analysis - Pauw, Karl (International Food Policy Research Institute, 2022)
This report examines the evolution of farm input subsidy programs in Ghana, with a focus on the Planting for Food and Jobs (PFJ) initiative, which was introduced in 2017 and replaced the Fertilizer Subsidy Program (FSP) that was launched in 2008. A review of PFJ implementation reports and other official data sources reveal that information on general program features, such as beneficiary numbers, subsidized input quantities, and program budget is readily available and useful for understanding program design and implementation. National crop production estimates are also reported annually, and these provide evidence of rapid output growth in the agricultural sector, especially within the cereals subsector. However, the implementing agency, the Ministry of Food and Agriculture (MoFA), lacks a system for closely monitoring and reporting PFJ program impacts at farm-level. Consequently, most of the published information on the marginal contribution of PFJ to national crop output is based on simulations, which make strong assumptions about seeding rates, fertilizer use by crop, and input use efficiency on beneficiary farms. With this drawback in mind, these simulations show that PFJ contributed substantially to crop output growth, a result which is not implausible considering the quantities of inputs provided, but one that requires further on-farm validation. Recommendations are offered around beneficiary targeting, interpretation of employment impacts, and the need for regular monitoring of farm-level impacts, all of which will help improve transparency of the program.